Revisiting principles of partnership working in the third space - Julie Blackwell Young; Sarah Parkes (Journal of Learning Development in Higher Education)
The COVID-19 pandemic catalysed significant shifts within higher education, prompting institutions to re-evaluate their approaches to partnership working. Collaborative efforts across institutional domains gained prominence, underlining the strategic importance of third-space professionals in facilitating agile decision-making and solution implementation. Here, they demonstrated resilience and adaptability, navigating the pandemic’s complexities while addressing the tandem feelings of messiness and uncertainty. They cultivated open mindsets and embraced a playful praxis, one emergent as an essential strategy for fostering trust and facilitating social learning amidst change. However, recognition and reward for such professionals remain complex, being at times hindered by the fluidity of their roles and fragmented nature of institutional acknowledgment. Our contention is that the culture evident during the pandemic that fostered meaningful collaborative practices and amplified third-space professionals is in danger of being lost.